2017
DOI: 10.1521/pedi_2017_31_276
|View full text |Cite
|
Sign up to set email alerts
|

Altered Empathy for Psychological and Physical Pain in Borderline Personality Disorder

Abstract: Many patients with borderline personality disorder (BPD) experience difficulties in empathizing with others and are sensitive to social exclusion. Accordingly, the authors developed a novel Social Interaction Empathy Task to examine empathy for physical and psychological pain from first- and third-person perspectives. Fifty female patients with BPD and forty-eight controls matched for age and gender were included. Alexithymia was also measured. Patients with BPD rated neutral and psychologically painful situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
4
21
0
1
Order By: Relevance
“…Repeated measures ANOVA with the covariates IQ and age revealed main effects and interactions, similar to results reported in previous studies using the SIET in patients with BPD ( 38 , 39 ). Specifically, we detected a three-way interaction of condition * group (BPD/HC) * genotype [ F (1.85) = 3.46; p = 0.036].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Repeated measures ANOVA with the covariates IQ and age revealed main effects and interactions, similar to results reported in previous studies using the SIET in patients with BPD ( 38 , 39 ). Specifically, we detected a three-way interaction of condition * group (BPD/HC) * genotype [ F (1.85) = 3.46; p = 0.036].…”
Section: Resultssupporting
confidence: 85%
“…The Social Interaction Empathy Task (SIET) was developed by our group as described elsewhere ( 38 , 39 ). In short, the paradigm investigates empathy for physical or somatic and psychological pain in one paradigm.…”
Section: Methodsmentioning
confidence: 99%
“…This is especially relevant, since alexithymia seems to be a mediating factor with respect to the link of attachment problems and the development of BPD [ 21 ]. Furthermore, alexithymia also mediates the effect of trauma on altered empathy-for-pain in BPD [ 31 ]. Crucially for patients with BPD, alexithymia is strongly associated with self-harm in women [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning its clinical relevance, alexithymia has been shown to be prognostically relevant for psychotherapy outcome [ 3 ]. Another limiting factor of the present study concerns the lack of emotional challenges during EEG measurement, because it is known that emotional tasks or other stressors may impact on frontal asymmetry [ 12 , 31 , 33 35 ]. This might be worth considering in future research.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with Ridings and Lutz-Zois (2014) , who found that alexithymia correlated with both emotional dysregulation, and BPD tendencies. Regarding a mechanistic link between alexithymia and empathy, Flasbeck et al (2017) found that the effect of early life adversity on empathy for psychological pain was mediated by alexithymia in BPD. Overall, while significant work would be required to scrutinize this speculative IST prediction of the link between affective dysregulation, alexithymia, and diminished empathy, the purpose here is to highlight the utility of IST, and the potential role of alexithymia in BPD empathic deficits.…”
Section: The Role Of the Insula In Alexithymia And Empathy Deficits Amentioning
confidence: 99%